(untitled) (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe the status of infections and clinical characteristics of patients with urinary tract infections (UITs) at Tra Vinh General Hospital. Materials and Methods: A descriptive cross-sectional study design was used, examining the medical records of 132 patients diagnosed with urinary tract infections. Bacterial strains were identified and phenotyped using the Vitek 2 system. Results were recorded in the medical records. Results: The female to male ratio of UTIs was 1.69:1; the most common age group is over 60 years old. The most common causative agents are Gram negative bacteria, with E. coli accounting for 51.61% and K. pneumoniae for 16.12%. Common comorbidities include hypertension and diabetes mellitus. Clinical symptoms include fever in 25.76%, no fever 74.24% of cases; urinary tract symptoms: frequent urination (48.48%), difficulty urinating (12.12%), painful urination (11.36%), urinary retention and hematuria (9.09%), cloudy urine (5.3%), and other urinary symptoms (6.06%). Conclusion: Prioritizing urine culture and bacterial identification before prescribing antibiotics is essential to accurately determine the causative agent and ensure effective treatment.